2013
DOI: 10.1002/elan.201200489
|View full text |Cite
|
Sign up to set email alerts
|

Low nM Detection Limits at Porous 1–3 nm Thick Membrane‐Coated Nanostructured Microdisk Electrodes

Abstract: Low (15 nM) limits of detection (LOD) of dopamine were obtained at porous 1–3 nm‐thick overoxidized polypyrrole (OPPY) membrane‐coated microdisk carbon fiber electrodes of small size (r=3.5 µm). The excellent mass transport through the porous OPPY membrane (efficiency as good as solution transport) contributes to the low LOD, together with dopamine preconcentration in the membrane. Structural characterization of the membrane coated electrodes confirms the contribution of membrane nanostructure to the high sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…For instance, many studies have demonstrated that overoxidized polypyrrole films exhibit molecular-sieve properties and such films have been used to fabricate glucose, alcohol, hydrazine, and dopamine sensors [25][26][27][28][29][30][31][32]. A demonstration of an organic electronic ion pump containing parts made of overoxidized PEDOT:PSS (poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate)) was provided in refs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many studies have demonstrated that overoxidized polypyrrole films exhibit molecular-sieve properties and such films have been used to fabricate glucose, alcohol, hydrazine, and dopamine sensors [25][26][27][28][29][30][31][32]. A demonstration of an organic electronic ion pump containing parts made of overoxidized PEDOT:PSS (poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate)) was provided in refs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many studies have demonstrated that overoxidized polypyrrole films exhibit molecular-sieve properties, and such films have been used to fabricate glucose, alcohol, hydrazine, and dopamine sensors [29,[32][33][34][35][36]. (Over)oxidized PEDOT films were successfully used for sensing perchlorate [37].…”
Section: Introductionmentioning
confidence: 99%
“…According to [38] overoxidized poly (3,4-ethylenedioxythiophene) film-modified screen-printed carbon electrodes exhibited superior sensitivity and selectivity to dopamine. However, the basis for the observed selectivity of overoxidized polymer films is still not entirely clear [24,36,39].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many studies have demonstrated that overoxidized polypyrrole films exhibit molecular-sieve properties, and such films have been used to fabricate glucose, alcohol, hydrazine, and dopamine sensors [25][26][27][28][29][30][31][32]. (Over)oxidized PEDOT films were successfully used for sensing perchlorate [33].…”
Section: Introductionmentioning
confidence: 99%
“…According to [34] overoxidized poly(3,4-ethylenedioxythiophene) film-modified screen-printed carbon electrodes exhibited superior sensitivity and selectivity to dopamine. However, the basis for the observed selectivity of overoxidized polymer films is not entirely clear [32,35,36].…”
Section: Introductionmentioning
confidence: 99%